Feasibility study of welding dissimilar Advanced and Ultra High Strength Steels - Bayock FN; Kah P; Salminen A; Belinga M; Yang XC (DE GRUYTER POLAND SP Z O O, 2022)
This study concerns the weldability of dissimilar Ultra high-strength steel (UHSS) and advanced high-strength steel (AHSS), which is used in the modern machine industry. The materials offered superior strength as well as relatively low weight, which reduces microstructure contamination during a live cycle. The choice of the welding process base of the base material (BM) and welding parameters is essential to improve the weld joint quality. S700MC/S960QC was welded using a gas metal arc welding (GMAW) process and overmatched filler wire, which was performed using three heat input (7, 10, and 15 kJ/cm). The weld samples were characterized by a Vickers-hardness test, scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS). The test reveals a decrease of softening areas in the HAZ and the formation of the stable formation of Bainite-Ferrite for S700MC and Bainite-martensite for S960QC when the heat input of 10 kJ/cm is used. It is recommended to use the GMAW process and Laser welding (Laser beam-MIG), with an optimal welding parameter, which will be achieved a high quality of manufacturing products.